Twenty-four Hour Holter Monitoring in Finishing Cattle Housed Outdoors - D. A. Frese; J. D. Thomason; C. D. Reinhardt; S. J. Bartle; D. N. Rethorst; G. H. Loneragan; E. F. Schwandt; D. U. Thomson (Kansas Agricultural Experiment Station Research Reports, 2017)
Ambulatory electrocardiogram monitoring, in the form of Holter monitoring, has been used in human and veterinary medicine for decades as an aid in the diagnosis and determination of appropriate therapy of heart rhythm disturbances. Within veterinary medicine, Holter monitors have been primarily used in companion animal species, yet little attention has been given to food animal species. Moreover, the heart rhythm in clinically normal cattle fed high concentrate diets and housed outdoors in confined drylot facilities has not been previously reported. In order to properly identify pathologic arrhythmias in cattle, the normal rhythm and arrhythmia prevalence in healthy cattle should be defined. Most prior reports of arrhythmia in cattle have been recordings of relatively shorter duration and in animals that were hospitalized or being handled for various reasons. Therefore, the objective of this study was to determine normal Holter monitor registrations including heart rate, rhythm, number of ventricular premature complexes, and atrial premature complexes in unrestrained finishing Angus steers.
Keywords: cattle; electrocardiogram; Holter